Verification and Validation of Transient Body Force in GOTHIC for Spent Fuel Pool Response to Seismic Events and Other Applications. (2nd January 2022) - Skelton, P. C.; Lane, J. W.; George, T. L.; Claybrook, S. W.
Abstract: Post Fukushima the U.S. Nuclear Regulatory Commission issued an Order on Spent Fuel Instrumentation (EA-12-051) requiring all U.S. nuclear plants to install spent fuel pool (SFP) water level monitoring instrumentation and ensure the instrument would remain functional following a safe shutdown earthquake (SSE). The structural integrity analysis requires an assessment of the hydrodynamic loads and wave impact forces that the instrument is subjected to during an SSE. Modeling and simulation of the SFP response to an SSE can provide this type of information if the simulation tool is able to capture the important physical phenomena, such as seismic acceleration, surface wave formation, fluid velocities, and multidimensional effects. This paper describes the capabilities of GOTHIC TM that can be used to simulate the sloshing surface waves and subsurface fluid motion of an SFP in response to an earthquake. GOTHIC is a versatile, general-purpose, thermal-hydraulic software package for multiphase flow that is a hybrid between traditional system thermal-hydraulic and computational fluid dynamics codes. It includes a transient, variable body force capability to simulate multi-axis acceleration, and is therefore applicable to seismic events; movement experienced on ships, airplanes, or spacecraft; and other events with system acceleration. Also, since the gravitational constant can be adjusted, GOTHIC can model systems placed outside the Earth's atmosphere (e.g., spacecraft, space station, the Moon, or other extraterrestrial bodies). The variable body force capability makes GOTHIC well suited to model the hydrodynamic response of an SFP to a seismic event. This paper describes the governing equations that are solved by GOTHIC as they pertain to accelerating systems. A series of benchmarks covering a range of experiments for surface wave dynamics, acceleration-induced motion, and other important phenomena are presented to demonstrate the verification and validation of GOTHIC for these types of applications. Finally, results from a sample application of GOTHIC for SFP hydrodynamic response are presented that provide the necessary inputs for a structural integrity analysis.